Penerapan Aplikasi Google Meet dalam Perkuliahan Daring Mahasiswa PGMI pada Mata Kuliah Pengukuran Geometri - Tiara Nurhayati; Melly Andriani; Siti Fatonah (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
Pendidikan daring dibutuhkan untuk menghasilkan proses pembelajaran jarak jauh terbaik di masa pandemi Covid-19. Penelitian ini bertujuan menguraikan penerapan aplikasi Google Meet dalam perkuliahan daring mahasiswa PGMI pada mata kuliah Pengukuran Geometri selama pandemi Covid-19. Penelitian berjenis kuantitatif ini dilakukan pada 30 mahasiswa PGMI angkatan 2020 kelas A. Hasil penelitian mengindikasikan bahwa perkuliahan melalui aplikasi Google Meet sangat mudah diakses oleh beberapa mahasiswa PGMI. Beberapa mahasiswa menyatakan bahwa lembar kerja mahasiswa berisi materi perkuliahan dapat dipahami dengan mudah. Sementara itu, terdapat 23 mahasiswa yang setuju dan 17 mahasiswa yang tidak setuju terhadap efektifitas penerapan aplikasi Google Meet dalam proses pembelajaran. This study aims to describe the implementation of google meet during online lectures for PGMI students in the Geometry Measurement course during the Corona virus pandemi. The subjects of this research are PGMI students class A class of 2020 with 30 students. This type of research uses quantitative research. This study describes the implementation of lectures using google meet. Information on research results through google meet in PGMI student lectures is very easily accessible to some students, on the other hand, who face student difficulties. In delivering the Student Worksheet material during lectures using Google Meet, several students gave a statement that they strongly agreed that the Student Worksheet was able to be understood and interpreted well and easily. The effectiveness of using the Google Meet application in lectures, 23 students stated that they were very able to follow the teaching and learning process, while 17 students said they did not agree with the effectiveness of the teaching and learning process. Students who cannot understand the material during the teaching and learning process are sometimes constrained by the signal being cut off due to rain or bad weather. So, the teacher makes and sends Student Worksheets via grup WhatsApp before the online teaching and learning process is carried out and students can learn first and when there is some material that cannot be understood it can be discussed during a meeting via google meet. Assessment in online lectures through Google Meet can also be assessed through question and answer interactions, discussions, and presentations of the questions contained in student worksheets.